Сross-cultural competency during training Ukrainian as a foreign language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article clarifies a concept “cross-cultural competency”, defines the structure of cross-cultural competency and analyses the stages of its formation.
Keywords: competency; competence; cross-cultural competency; cross-cultural contacts